Chinese Word Order in the Comparative Sino-Tibetan and Sociotypological Contexts - Yurayong C. (2023)
The present study discusses typology and variation of word order patterns in nominal and verb structures across 20 Chinese languages and compares them with another 43 languages from the Sino-Tibetan family. The methods employed are internal and external historical reconstruction and correlation studies from linguistic typology and sociolinguistics. The results show that the head-final tendency is a baseline across the family, but individual languages differ by the degree of head-initial structures allowed in a language, leading to a hybrid word order profile. On the one hand, Chinese languages consistently manifest the head-final noun phrase structures, whereas head-initial deviants can be explained either internally through reanalysis or externally through contact. On the other hand, Chinese verb phrases have varied toward head-initial structures due to contact with verb-medial languages of Mainland Southeast Asia, before reinstalling the head-final structures as a consequence of contact with verb-final languages in North Asia. When extralinguistic factors are considered, the typological north-south divide of Chinese appears to be geographically consistent and gradable by the latitude of individual Chinese language communities, confirming the validity of a broader typological cline from north to south in Eastern Eurasia.